Dietary chlorogenic acid supplementation to alleviate intestinal damage in juvenile American eel (Anguilla rostrata) under histamine stress - Guo-He Cai; Zi-Yan Hu; Yi-Tong Guo; Zhi-Xue Guo; Yun-Zhang Sun; Shao-Wei Zhai (Aquaculture Reports)
Eels (Anguilla spp.) are carnivorous fish with high protein requirements. A major challenge in eel aquaculture is the use of low-cost red fishmeal, which, due to its high histamine content, causes slow growth, reduced immunity and intestinal damage in eels, rendering it unsuitable as a replacement for white fishmeal. Chlorogenic acid (CGA), a natural polyphenol with antioxidant and anti-inflammatory properties, has been shown in rodent and pig studies to enhance gut barrier integrity, reduce intestinal inflammation, and promote growth. This study utilized the juvenile American eel (Anguilla rostrata), a major aquaculture species in China, as the experimental model. A total of 264 juvenile eels (initial weight: 14.33 ± 0.57 g) were randomly assigned to four treatment groups: CON (control, basal diet), H (basal diet + 650 mg/kg histamine), H + CGA200 (H + 200 mg/kg CGA), and H + CGA600 (H + 600 mg/kg CGA). The results indicated that compared to the H group, the CGA supplementation groups exhibited significantly improved growth performance (FBW, WGR, SGR, FR) and serum immune parameters (IgM, C3) (P < 0.05). Intestinal health assessments revealed that CGA suppressed the expression of histamine receptor gene hrh1 under histamine-induced stress (P < 0.05), reduced the expression of pro-inflammatory genes (NF-κB, IL-6, TNF-α, IFN-γ) (P < 0.05), and increased the activity of intestinal protease and lipase (P < 0.05). Furthermore, CGA improved intestinal morphology, modulated the gut microbiota structure, and increased the abundance of beneficial bacteria (P < 0.05). These findings suggest that 200 mg/kg CGA can mitigate the negative effects of high histamine in fishmeal on eel growth, intestinal health and Immune function, could be used as an additive in red fishmeal to reduce aquaculture costs.